Tree seed traits’ response to monsoon climate and altitude in Indian subcontinent with particular reference to the Himalayas - Singh, Surendra P. (Ecol Evol, 2017)
Seed traits are related to several ecological attributes of a plant species, including its distribution. While the storage physiology of desiccation‐sensitive seeds has drawn considerable attention, their ecology has remained sidelined, particularly how the strong seasonality of precipitation in monsoonal climate affects their temporal and spatial distribution. We compiled data on seed mass, seed desiccation behavior, seed shedding, and germination periodicity in relation to monsoon and altitude for 198 native tree species of Indian Himalayas and adjoining plains to find out (1) the adaptive significance of seed mass and seed desiccation behavior in relation to monsoon and (2) the pattern of change in seed mass in relation to altitude, habitat moisture, and succession. The tree species fall into three categories with respect to seed shedding and germination periodicities: (1) species in which both seed shedding and germination are synchronized with monsoon, referred to as monsoon‐synchronized (MS, 46 species); (2) species in which seed germination is synchronized with monsoon, but seeds are shed several months before monsoon, referred to as partially monsoon‐synchronized (PMS, 112 species); and (3) species in which both shedding and germination occur outside of monsoon months, referred to as monsoon‐desynchronized (MD, 39 species). The seed mass of MS species (1,718 mg/seed) was greater than that of PMS (627 mg/seed) and MD (1,144 mg/seed). Of the 40 species with desiccation‐sensitive seeds, 45% belong to the MS category, almost similar (approx. 47%) to woody plants with desiccation‐sensitive seeds in evergreen rain forests. Seed mass differed significantly as per seed desiccation behavior and successional stage. No relationship of seed mass was found with altitude alone and on the basis of seed desiccation behavior. However, seed mass trend along the altitude differed among monsoon synchronization strategies. Based on our findings, we conclude that in the predicted climate change (warming and uncertain precipitation pattern) scenario, a delay or prolonged break‐spell of monsoon may adversely affect the regeneration ecology of desiccation‐sensitive seed‐bearing species dominant over large forest areas of monsoonal climate.